A Study on the Purpose of Using Social Networking Sites Among UiTM Kedah Students / Ainur Fathiah Hamsan and Nor Syafawati Ab Wahab - Hamsan, Ainur Fathiah; Ab Wahab, Nor Syafawati (2010)
Social networking sites such as Facebook and MySpace currently become a part of the social lifestyle activities for the means of online communication in this modern era. The social networking sites are not only used by the teenagers, but this new media is also being used by all age, background and status such as business people, politicians, celebrities and others. Realizing on the importance of the social networking activities today, this study being conducted to examine what are the reasons and purposes of the students in UiTM Kedah use the social networking sites concerning on education, entertainment and connectivity functions. This study will evaluate and reveal what is the main purpose among of them in using the social networking sites